The innovation discourse in costarrican press: functional use of the concept - Kiewit, Luis Diego Soto (2019)
This article reflects the different uses of the word innovation, in the Costa Rican written press, the emphasis is onits association with a specific context, seeking to identify legitimizing and delegitimizing uses. The discussion it isbased on the collection of news in two media (digital version), namely the newspapers: La Nación y El Financiero,during the first three months of 2015, 2016 and 2017. This reflection is positioned from the Critical DiscourseAnalysis approach, specifically, it is a pragmatic analysis of the various news, because the interest of knowledge is inthe relationship between innovation and context, within the text. The document presents that strategic, tendentiousand polysemic use with which the word innovation is used in the different news, showing that more than a perspectiveof innovation that is to be promoted, this is the concept that allows supporting proposals or concerns about thenational reality.